KONTRIBUSI PEMBINAAN AKHLAK DALAM MENANAMKAN SELF-CONTROL SISWA SEKOLAH DASAR NEGERI - Surawan Surawan; Lia Norvia (SITTAH: Journal of Primary Education, 2022)
This research aims to determine the contribution of moral coaching in instilling students' self-control. The research uses qualitative research methods. Data collection techniques using interviews and direct observation. The research subjects were students and teachers of Islamic religious education at State Elementary Schools in Palangka Raya City and an expert from outside the school. The results of this study indicate that moral coaching on students' self-control abilities leads to three positive impacts; changes in mindset, changes in principles, and changes in behavior. The three positive impacts received responses from families and communities through family enthusiasm and community support. Overall, it can be concluded that moral coaching can provide positive changes to students' self-control. This research is expected to have implications for strengthening school coaching activities, which further activates the role of parents and the community so that good changes in students can be actualized in daily life and the implementation of school coaching programs becomes optimal.